AGE DIFFERENCES IN THE EFFECTIVENESS OF DIFFERENT REINFORCEMENT COMBINATIONS ON THE ACQUISITION AND EXTINCTION OF A SIMPLE CONCEPT LEARNING PROBLEM. - Meyer, William J.; Seidman, Stanley B. (Child Development, 1960)
The effectiveness of four combinations of reinforcers at two development levels was analyzed in this experiment. The combinations were Right-Wrong, Right-Nothing, Nothing-Wrong, and Buzzer-Nothing. It was assumed that the nothing aspects of these reinforcers would be sufficiently ambiguous to permit age differences in sensitivity to reinforcing cues to function. The Ss, age 4 to 5 and 8 to 9, were required to learn the concept "larger than" by responding to pairs of blocks. A significant age X treatments effect for the acquisition series was interpreted as meaning that the effectiveness of these reinforcers is related to level of development. The Nothing-Wrong group performed significantly better on the extinction series than the other groups. This latter finding was interpreted as meaning that nothing when paired with wrong acquires positive reinforcement value.